(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2007)
The antinociceptive activity of the crude extract and fractions of Stryphnodendron adstringens (Martius) Coville (barbatimão) was evaluated. Three experimental models of pain induction were used: abdominal writhing, formalin, and hot plate. The results demonstrated an antinociceptive effect of barbatimão in the experimental models of writhing induced by acetic acid and pain induced by formalin. However, the extracts did not significantly alter latency time on the hot plate in mice. These results suggest that barbatimão extract has a peripheral antinociceptive effect.